2016
DOI: 10.1590/s1679-45082016md3557
|View full text |Cite
|
Sign up to set email alerts
|

Advances in lung ultrasound

Abstract: Ultrasound examination of the chest has advanced in recent decades. This imaging modality is currently used to diagnose several pathological conditions and provides qualitative and quantitative information. Acoustic barriers represented by the aerated lungs and the bony framework of the chest generate well-described sonographic artifacts that can be used as diagnostic aids. The normal pleural line and A, B, C, E and Z lines (also known as false B lines) are artifacts with specific characteristics. Lung consoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 9 publications
(10 reference statements)
0
46
0
9
Order By: Relevance
“…LUS is an alternative to direct radiographs in emergency departments to visualize lung pathologies. It is used to confirm endotracheal tube placement and for visualization of pneumothorax, alveolar pathologies, lung consolidation, and pleural effusion (7). Studies have shown that LUS is superior to direct radiographs in visualizing alveolar pathologies (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…LUS is an alternative to direct radiographs in emergency departments to visualize lung pathologies. It is used to confirm endotracheal tube placement and for visualization of pneumothorax, alveolar pathologies, lung consolidation, and pleural effusion (7). Studies have shown that LUS is superior to direct radiographs in visualizing alveolar pathologies (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant to those regions where reference samples are not available and even more so to those regions where historic admixture has complicated the simple assignment of skeletal remains to relatively well characterised groups. This scenario applies noticeably in Brazilian forensic anthropology (Francisco 2015), where historic immigration and intermarriage has led to admixture between groups of Native South American, African, European and-more recently-Arab and Japanese ancestry. Figure 14 illustrates a reconstruction of a Brazilian individual of mixed ancestry, successfully leading to identification of a missing person.…”
Section: Computerised Approachesmentioning
confidence: 97%
“…E lines are well-defined and can also erase A lines, so they can be mistaken for true B lines. 20 Z lines are common artifacts seen in more than 80% of the population and may be mistaken for coalescent B lines described above. Z lines are vertical, bundle-like shaped lines arising from the pleural line; however, they are ill-defined, they do not erase a lines, and are not perfectly synchronous with respiratory movements.…”
Section: Linesmentioning
confidence: 97%
“…(Figure 8, 9) The artefact consists of a trail of dense echoes that resembles a distally oriented comet-tail. 20 B lines indicate filling of intralobular or interlobular septa and are often seen in pulmonary edema and interstitial lung diseases. 8,11 Thickened B lines may fuse together to form coalescent B lines representing peripheral lung ground glass opacities seen in high resolution computed tomography (cT).…”
Section: Linesmentioning
confidence: 99%
See 1 more Smart Citation